Primary care physicians' perspective on financial issues and adult immunization in the Era of the Affordable Care Act. Issue 4 (23rd January 2017) - Hurley, Laura P.; Lindley, Megan C.; Allison, Mandy A.; Crane, Lori A.; Brtnikova, Michaela; Beaty, Brenda L.; Snow, Megan; Bridges, Carolyn B.; Kempe, Allison
Abstract: Background: Financial barriers to adult vaccination are poorly understood. Our objectives were to assess among general internists (GIM) and family physicians (FP) shortly after Affordable Care Act (ACA) implementation: (1) proportion of adult patients deferring or refusing vaccines because of cost and frequency of physicians not recommending vaccines for financial reasons; (2) satisfaction with reimbursement for vaccine purchase and administration by payer type; (3) knowledge of Medicare coverage of vaccines; and (4) awareness of vaccine-specific provisions of the ACA. Methods: We administered an Internet and mail survey from June to October 2013 to national networks of 438 GIMs and 401 FPs. Results: Response rates were 72% (317/438) for GIM and 59% (236/401) for FP. Among physicians who routinely recommended vaccines, up to 24% of GIM and 30% of FP reported adult patients defer or refuse certain vaccines for financial reasons most of the time. Physicians reported not recommending vaccines because they thought the patient's insurance would not cover it (35%) or the patient could be vaccinated more affordably elsewhere (38%). Among physicians who saw patients with this insurance, dissatisfaction ('very dissatisfied') was highest for payments received from Medicaid (16% vaccine purchase, 14% vaccine administration) and Medicare Part B (11% vaccine purchase, 11% vaccine administration). Depending on the vaccine, 36–71% reported not knowing how Medicare covered the vaccine. Thirty-seven percent were 'not at all aware' and 19% were 'a little aware' of vaccine-specific provisions of the ACA. Conclusions: Patients are refusing and physicians are not recommending adult vaccinations for financial reasons. Increased knowledge of private and public insurance coverage for adult vaccinations might position physicians to be more likely to recommend vaccines and better enable them to refer patients to other vaccine providers when a particular vaccine or vaccines are not offered in the practice.